Deeper Insight into the Six‐Step Domino Reaction of Aldehydes with Malononitrile and Evaluation of Antiviral and Antimalarial Activities of the Obtained Bicyclic Products. Issue 3 (26th April 2017) - Bock, Christina M.; Parameshwarappa, Gangajji; Bönisch, Simon; Bauer, Walter; Hutterer, Corina; Leidenberger, Maria; Friedrich, Oliver; Marschall, Manfred; Kappes, Barbara; Görling, Andreas; Tsogoeva, Svetlana B.
Abstract: The straightforward and efficient synthesis of complex aza‐ and carbobicyclic compounds, which are of importance for medicinal chemistry, is a challenge for modern chemical methodology. An unprecedented metal‐free six‐step domino reaction of aldehydes with malononitrile was presented in our previous study to provide, in a single operation, these bicyclic nitrogen‐containing molecules. Presented here is a deeper investigation of this atom‐economical domino process by extending the scope of aldehydes, performing post‐modifications of domino products, applying bifunctional organocatalysts and comprehensive NMR studies of selected domino products. The thermodynamic aspects of the overall reaction are also demonstrated using DFT methods in conjunction with a semi‐empirical treatment of van der Waals interactions. Furthermore, biological studies of seven highly functionalized and artemisinin‐containing domino products against human cytomegalovirus (HCMV) and Plasmodium falciparum 3D7 are presented. Remarkably, in vitro tests against HCMV revealed five domino products to be highly active compounds (EC50 0.071–1.8 μm ), outperforming the clinical reference drug ganciclovir (EC50 2.6 μm ). Against P. falciparum 3D7, three of the investigated artemisinin‐derived domino products (EC50 0.72–1.8 nm ) were more potent than the clinical drug chloroquine (EC50 9.1 nm ). Abstract : The domino effect : Investigations of the metal‐free six‐step domino reaction of aldehydes with malononitrile are reported, extending the scope of aldehydes and organocatalysts. NMR studies of selected products and DFT calculations of the thermodynamics of this reaction are presented. Evaluation of seven highly functionalized and artemisinin‐containing domino products against human cytomegalovirus and Plasmodium falciparum 3D7 reveals high activity, with the compounds outperforming the clinical drugs ganciclovir and chloroquine.